Agent-based model of system-wide implications of funding risk - Grzegorz Hałaj (European Central Bank (ECB), 2018)
Liquidity has its systemic aspect that is frequently neglected in research and risk management applications. We build a model that focuses on systemic aspects of liquidity and its links with solvency conditions accounting for pertinent interactions between market participants in an agent-based modelling fashion. The model is confronted with data from the 2014 EU stress test covering all the major banking groups in the EU. The potential amplification role of asset managers is taken into account in a stylised fashion. In particular, we investigate the importance of the channels through which the funding shock to financial institutions can spread across the financial system.
Keywords: G11; G21; C61; 330; liquidity; systemic risk; ABM